The Influence of Training and Motivation on Employee Performance with Job Satisfaction as a Mediating Variable (Study at PT. BPR Gunung Kawi) - Indira Rizma Shanti; Tristiana Rijanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Abstract consists of a maximum of 250 words, written in English with Times New Roman font size 11 in one space. This study aims to analyze the influence of Training (X1) and Motivation (X2) on Employee Performance (Y2) with Job Satisfaction (Y1) as mediation variables in PT. BPR Gunung Kawi. This study uses primary data obtained from respondents through questionnaires. The research population consists of the entire staff of PT.BPR Gunung Kawi, a total of 150 people. The sampling method used is Purposive Sampling. The sample consists of 120 permanent employees with at least 2 years of work experience with a minimum level of SLTA education. Data analysis techniques include validity tests, reliability tests, t-tests, and sobel tests for mediation test analysis. The data analysis was carried out using SPSS 26.0. The results of the hypothesis test used regression analysis which showed that Training and Motivation had a positive and significant impact on Job Satisfaction. Training had no significant effect on Employee Performance. Motivation and Job Satisfaction had a significant and positive impact on Employee Performance.